Opt‐Out Design for an Observational Toxicology Study Involving Intoxicated Patients at a Dance Music Event. Issue 5 (8th September 2021) - Calle, Paul; Blanckaert, Peter; Lemoyne, Sabine; Rubens, Robert
Abstract: At electronic dance music events in Belgium in 2013 to 2015, seemingly intoxicated patients were included without their informed consent in an observational toxicology study when the attending physicians determined that they needed treatment with an intravenous line. All included patients received an information letter inviting them to contact the principal investigator (PI) to obtain more information about the study and/or to inform the PI that they wanted to be excluded from it. Overall, 238 patients were included in the study. Nine participants (4%) responded to the information letter, either on their own or through their parent; none of them asked to be excluded from the study. All respondents expressed their gratitude for the information they received. The opt‐out study design seemed to be acceptable to the patient‐participants, and it provided a fuller picture of the drug‐related medical incidents at such music events than what could likely be achieved through a study that includes only people who explicitly choose to participate. These findings may help institutional review boards when evaluating study designs involving recreational drug use, especially at electronic dance music events. Nevertheless, we warn against extrapolation to other settings where informed consent is difficult to obtain.